Macroeconomic factors affecting inward cross-borders mergers and acquisitions in selected developing countries - Yoong, Wai Kem (2017)
This study examines the effect of 5 macroeconomic factors on inward cross-border merger and acquisition in 11 developing countries within the periods from the year 2001 to 2015. This research examines the hypotheses by employing Unit Root Test, Descriptive Statistics, Panel Least Squares (OLS) and Correlation Test. The finding indicates that there is a negative relationship between three macroeconomic factors (inflation, exchange rate and interest rate) and the numbers of the inward cross-border mergers and acquisitions. There are positive relationship between another one macroeconomic factors (Gross Domestic Products) and the numbers of the inward cross-border mergers and acquisitions. This implies that high percentage of inflation, exchange rate and interest rate lead to lower the number of inward cross-border mergers and acquisitions. Moreover, low percentage of Gross Domestic Products leads to lower the number of inward cross-border mergers and acquisitions. Stock Price Index (SPI) is insignificant negative relationship with inward cross border M&A. This indicates that higher values in the Net Present Values will able to generate favorable values of inward cross-border mergers and acquisitions of the countries in future, in which support the signaling theory.